Social movements (popular, labor, and peasant) in the 1970s - Granda Aguilar, Víctor (Revolutionary nationalism: The 1970s and the Contemporary History of Ecuador, 2026)
It analyzes the struggles of workers, peasants, and students against the industrialist model. It examines everything from Velasco’s authoritarianism to Rodríguez Lara’s “revolutionary nationalism” and the regression of the Triumvirate. It highlights milestones such as the first FUT strike, the limited agrarian reform, and the Aztra massacre in 1977. The text explains how the National Security Doctrine and Operation Condor were used to suppress union unity and halt the return to constitutional rule.